2006
DOI: 10.1111/j.1365-2036.2006.03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: Helicobacter pylori eradication for the prevention of gastric cancer

Abstract: SUMMARY BackgroundHelicobacter pylori is recognized as one of the most significant risk factors for gastric cancer, and H. pylori eradication has been proposed as a possible primary chemo-preventive strategy to reduce gastric cancer incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 62 publications
2
84
1
2
Order By: Relevance
“…Hwang et al [95] reported that peptic ulcer patients had lower atrophy scores than patients with simple gastritis, whereas Brooks [96] reported that patients with gastric ulcer generally have more severe atrophy than do duodenal ulcer patients, and furthermore, Fuccio et al [11] reported that many patients with gastric ulcer also have atrophic gastritis or intestinal metaplasia. Hussein [1] has shown that gastric ulcer is associated with a high risk, but duodenal ulcer with a low risk, of gastric cancer, and patients with gastric ulcers typically have atrophic gastritis and corpus-predominant gastritis, whereas patients with duodenal ulcers have antral-predominant gastritis, but few atrophic changes.…”
Section: Failure To Notice Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al [95] reported that peptic ulcer patients had lower atrophy scores than patients with simple gastritis, whereas Brooks [96] reported that patients with gastric ulcer generally have more severe atrophy than do duodenal ulcer patients, and furthermore, Fuccio et al [11] reported that many patients with gastric ulcer also have atrophic gastritis or intestinal metaplasia. Hussein [1] has shown that gastric ulcer is associated with a high risk, but duodenal ulcer with a low risk, of gastric cancer, and patients with gastric ulcers typically have atrophic gastritis and corpus-predominant gastritis, whereas patients with duodenal ulcers have antral-predominant gastritis, but few atrophic changes.…”
Section: Failure To Notice Lesionsmentioning
confidence: 99%
“…Uemura et al [6] conducted a 5-year follow-up of many Japanese subjects with H. pylori infections and found that all those with duodenal ulcers were also infected with H. pylori; however, none of the patients with duodenal ulcer developed gastric cancer, although 3.4% of the patients with gastric ulcer did, and gastric cancer subsequently appeared in 5% of the patients with H. pylori infections. Fuccio et al [11] indicated that the risk of gastric cancer was higher in patients with gastric ulcer than in those with duodenal ulcer. Therefore, gastric cancer concomitant with duodenal ulcer appears to be very rare.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Fuccio, et al investigated this idea. 10 In previous work by them and others, it has been demonstrated that E-cadherin, a tumor suppressor gene, is aberrantly methylated in H. pylori infected gastric specimens as well as in gastric tumor specimens. A decrease in methylation of E-cadherin has been demonstrated after treatment of H. pylori infection, suggesting the possibility that methylation changes induced by infection can be mitigated by treatment directed against the bacteria.…”
Section: Inflammation and Methylation Changesmentioning
confidence: 97%
“…About 50% of the world population is affected with this bacterium. Although eradication of H. pylori has shown a benefi cial effect in experimental studies, metaanalyses have not found a signifi cant benefi t for human beings [4]. Only after endoscopic mucosal resection for early gastric cancer, eradication of H. pylori proved benefi cial to prevent metachronic gastric cancer [5].…”
mentioning
confidence: 99%